Acquired multifocal tufted angiomas in an immunocompetent young adult - Sudip Kumar Ghosh (Indian Journal of Dermatology, 2011)
Tufted angioma (TA) is a rare benign vascular neoplasm, localized to the skin and subcutaneous tissues, occurring primarily on the trunk and extremities of children. The lesions are usually asymptomatic but, rarely, paroxysmal painful episodes may be associated. The occurrence of eruptive TA is still rarer and had been described almost exclusively in association with immunocompromised states. We report here a case of acquired painful multifocal tufted angiomas on the face and neck in an immunocompetent young adult.